PHYSICAL ACTIVITY AND OLDER ADULTS - B. Tumanova (Trakia Journal of Sciences)
Physical activity among the older population of Bulgaria is a matter related to health prevention, improving the quality of life and recovery after illness. In this work, we present data from a study held with people aged 65-80 years, citizens of Sofia city. Our goal was to determine the place of physical exercise in their daily lives and the role of sports teacher for the formation of motivation in them for leading an active lifestyle. The analysis shows lack of information on the wide variety of motor activities suitable for this age group as well as low level of motivation for sport activities. We conclude that it is necessary to provide sources of information to the people of the third age, which will educate them about the benefits of the active way of life and what possibilities for access to various sports activities are there. Medium intensity workout or a daily walk outdoors would help not only to improve their fitness level but also to maintain the necessary mental health and social activity.